The Influence of Consumer Satisfaction on Loyalty at Destination Wedding By Bali Eve - Dewi, Luh Kadek Wulan Kusuma; Citrawati, Luh Putu; Swandewi, Ni Kadek (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of customer satisfaction (X) on loyalty (Y) at Destination Wedding by Bali Eve. Destination Wedding by Bali Eve is a company engaged in wedding planner services in Bali. Customer satisfaction is often closely related to the user experience when using a product or service. Consumer loyalty is inseparable from the satisfaction that the bride and groom have felt before. The method used in this research is quantitative with data analysis techniques Simple Linear Regression, T Test, and Coefficient of Determination (R2), with the SPSS Version 22 data processing application. The population in this study are consumers who have purchased services at Destination Wedding by Bali Eve. The number of respondents involved in this study was 53 people. The research instrument used is a questionnaire that has been tested for validity and reliability. The regression analysis results show Y = 4.523 + 0.220 (X). Based on the results of the t test, it shows that customer satisfaction (X) has a positive and significant effect on loyalty (Y). This means that the better customer satisfaction provided by Destination Wedding by Bali Eve, the higher the level of loyalty. Based on the Coefficient of Determination Test (R2), it is known that the customer satisfaction variable (X) has an effect of 59.6% on loyalty (Y) while 40.4% is influenced by other factors.